HUBUNGAN KUALITAS PEMULIHAN DENGAN EVALUASI KEPUASAN PASIEN PASCA OPERASI SC DENGAN METODE ERACS DI RSABB - Aminah Aatina Adhyatma; Rici Gusti Maulani; Hasibuan, Diwanisari (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2023)
Childbirth procedures C-section, usually induce inconvenience post-surgery for the patient such as pain, mobility and personal fulfillment difficulty, and a mother’s duty to nurse their newborn. Enhanced Recovery After Cesarean Surgery or ERACS is a series of treatments that could speed up the patient recovery after surgery, from preoperative preparation to the patient discharge. Some hospitals in Indonesia have conducted their own study regarding the correlation between patient recovery quality to patient’s satisfaction level, but RS Awal Bros Batam doesn’t have the study yet. This study was done using an observational method and quantitative approach using Chi square on 30 C-section patients who are using ERACS method. The study was conducted in Solandra Room, RS Awal Bros Batam from January – February 2023. The result showed 83.3% of the patients recovered well and 83.3% patients satisfied with ERACS method. Chi square statistic test showed that the recovery quality and the patient’s satisfaction is dependent on one another (p < 0.005). Therefore, there is a correlation between the patient’s recovery quality and their satisfaction level on C-section with ERACS method.